Trade openness, poverty, and sustainable development: Testing for causality using Dumitrescu-Hurlin approach - Adewale Musliudeen Balogun; Oluwaseyi Adedayo Adelowokan; Felix Odunayo Ajayi; Jimoh Sina Ogede (Journal of Enterprise and Development (JED), 2024)
Purpose — This research paper explores the causal links between trade openness, poverty, and sustainable development, shedding light on the potential impact of trade policies on poverty reduction and sustainable development in the Economic Community of West African States (ECOWAS) region.Method — We utilize the Dumitrescu-Hurlin (DH) panel causality test, a robust econometric approach capable of discerning the direction and magnitude of causal relationships among variables. We employ a comprehensive dataset spanning from 1986 to 2020, covering ECOWAS countries, to conduct a rigorous empirical analysis.Result — The empirical findings from the DH causality analysis reveal a unidirectional relationship between trade openness, human capital investment, and both sustainable development and poverty. Additionally, bidirectional causality relationships are observed between human capital investment and poverty. The results also highlight the absence of a consistent and uniform pattern of Granger causality between poverty and sustainability across individual West African economies. This heterogeneity underscores the need for customized policy approaches based on empirical evidence derived from country-specific causality analyses, rather than adopting one-size-fits-all solutions.Novelty  — This research stands out by exploring the causal connections among trade openness, poverty, and sustainable development within the Economic Community of West African States (ECOWAS) region. The adoption of the Dumitrescu-Hurlin (DH) panel causality test enhances the empirical analysis, offering a comprehensive understanding of both the direction and magnitude of these relationships.